Real-world use and accuracy of stress echocardiography: preliminary insights from the EVAREST study. (25th November 2020) - Woodward, W; McCourt, A; Dockerill, C; Ayres, L; Augustine, D; O'Driscoll, J; Sharma, R; Benedetto, E; Spagou, N; Tsiachristas, A; Upton, R; Leeson, P
Abstract: Background: Stress echocardiography is a widely used, non-invasive imaging modality used to identify prognostically significant coronary artery disease. High levels of accuracy have been reported, however this is highly dependent on operator training and image quality. There are currently limited data available on the accuracy of stress echo in every day clinical practice. Purpose: The EVAREST study links stress echo clinics in 30 NHS Hospital Trusts in England and therefore provides data to evaluate the performance and diagnostic accuracy of stress echo in "real-world" clinical practice. Methods: Analysis was performed on the first 7415 patients recruited prospectively between 2015 and January 2020. Participants are included if they have undergone stress echo to investigate for ischaemic heart disease. Data is collected on medical history and stress echo performance. Participants are followed up for 12 months through health records and patient phone call, with all outcomes undergoing expert adjudication. A positive cardiac outcome is defined as initiation of anti-anginal medications, ≥70% stenosis on coronary angiography, revascularisation, confirmed acute coronary syndrome or cardiac-related death. Results: Mean age of patients undergoing stress echo is 65±12.3 years and 56% are male. Average BMI is 28.9±5.6 kg/m 2 . 71.4% undergo dobutamine stress (DSE) and 28.4% exercise with <1% having a pacemaker-mediated stress. Contrast was used in 71.4% of studies. Stress echos were interpreted at time of clinic visit as positive for inducible ischaemia in 18.2% of patients. One-year outcome data is currently available for 1892 participants. Sensitivity and specificity for clinician prediction of a positive cardiac outcome was 88.7% and 94.4%, respectively. Positive and negative predictive value of stress echo was 76.4% and 97.6%, respectively. Conclusion: EVAREST provides unprecedented, large-scale information on the "real world" use and accuracy of stress echo across different healthcare settings in the UK, demonstrating performance consistent with best practice. Ongoing data collection will be used to evaluate sources of heterogeneity in the predictive accuracy of stress echo and identify optimal approaches to further improve performance. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Ultromics Ltd., Lantheus Ltd.